A highly sensitive and selective fluorescent probe for N2H4 in air and living cells. (18th September 2017) - Cui, Jie; Gao, Guanqing; Zhao, Hengzhi; Liu, Yazhou; Nie, Hailiang; Zhang, Xiaoling
Abstract : A new colorimetric and fluorescent probe developed for the sensitive and selective detection of N2 H4 in air and aqueous solution. Abstract : Hydrazine (N2 H4 ) is considered as an environmental contaminant and a potential carcinogen, and its large-scale application could pose a great threat to the environment and human health. In the present work, a new colorimetric and fluorescent probe NAA was developed for the sensitive and selective detection of N2 H4 in air and aqueous solution. The probe shows a selective response to N2 H4 against various interferences ( e.g., anions, cations, amines and small biomolecules) and a detection limit as low as 0.716 ppb (22.5 nM) far below the threshold limit value (10 ppb) of EPA. By observing the color and fluorescence changes, the test strip coated with NAA provides an economical and convenient tool for the rapid detection of N2 H4 gas. Moreover, the probe was proved to possess low cytotoxicity as well as good membrane permeability and thus shows great potential in N2 H4 imaging in living cells.